2018
DOI: 10.1002/2017gl076439
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Warm Water Volume Precursor of ENSO Events and its Interdecadal Variation

Abstract: A wind forced ocean model is used to decompose the equatorial Pacific warm water volume (WWV) between 1980 and 2016 into two components: the (i) adjusted wind response, which is found by letting the model evolve unforced for three months, and (ii) instantaneous wind response, which are the instantaneous WWV changes due to Ekman transports. Our results suggest that roughly half of WWV variability is only as predictable as the winds that drive the instantaneous change. Separate examinations of pre‐2000 and post‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
64
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 37 publications
8
64
0
1
Order By: Relevance
“…A recent study by Neske and McGregor (2018) attributes this asymmetry to an asymmetry in oceanic processes, with the discharged phase of the cycle dominated by the adjusted wave dynamics and the recharged phase dominated by the instantaneous wind-induced Ekman mass transport. A recent study by Neske and McGregor (2018) attributes this asymmetry to an asymmetry in oceanic processes, with the discharged phase of the cycle dominated by the adjusted wave dynamics and the recharged phase dominated by the instantaneous wind-induced Ekman mass transport.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Neske and McGregor (2018) attributes this asymmetry to an asymmetry in oceanic processes, with the discharged phase of the cycle dominated by the adjusted wave dynamics and the recharged phase dominated by the instantaneous wind-induced Ekman mass transport. A recent study by Neske and McGregor (2018) attributes this asymmetry to an asymmetry in oceanic processes, with the discharged phase of the cycle dominated by the adjusted wave dynamics and the recharged phase dominated by the instantaneous wind-induced Ekman mass transport.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…However, recent studies show that the recharge oscillator dynamics is a less effective determinant of ENSO variability after the year 2000 (e.g., GM2016;McPhaden, 2012;Neske & McGregor;, related to the more frequent occurrence of CP El Niño events (Lee & McPhaden, 2010;Wen et al, 2014;Xiang et al, 2013). Our results confirm previous studies about the role of TCFs related to recharge oscillator dynamics in determining the asymmetry in El Niño-La Niña duration and provide robust evidence from the perspective of a detailed temperature variance budget analysis for the first time.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…On this front, Neske and McGregor (2018) showed that WWBs themselves can create a significant WWV response that can be decomposed into two components: the "adjusted response" (which relies on slow ocean dynamics associated with Rossby wave reflection as depicted by the recharge oscillator theory) and the "instantaneous response" (which represents surface Ekman transport in response to WWB). The adjusted response is identified as the source of predictability and it has weakened since the start of the 21 st Centurythe reason for this decline remains unclear but may be associated with a shift in the background climate toward the cold phase of the IPO (Zhao et al 2016) through modulation of governing ENSO processes (e.g., WWBs, WWV, etc.).…”
Section: Enso Predictionmentioning
confidence: 99%
“…However, this phase‐lag relationship between the WWV and ENSO SST has experienced a significant shift around 2000 with the lead time being shortened from approximately two to three to approximately one seasons (Bosc & Delcroix, ; Bunge & Clarke, ; Horii et al, ; McPhaden, ; Neske & McGregor, ). Also, operational ENSO predictability in the recent two decades declined to an effective lead time of only one season, much shorter than the average predictability before 2000 (Hendon et al, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%